The age of acquiescence : the life and death of American resistance to organized wealth and power - Fraser, Steve, 1945- (New York : Little, Brown and Company, 2015)
"A groundbreaking investigation of how and why, from the 18th century to the present day, American resistance to our ruling elites has vanished. From the American Revolution through the Civil Rights movement, Americans have long mobilized against political, social, and economic privilege. Hierarchies based on inheritance, wealth, and political preferment were treated as obnoxious and a threat to democracy. Mass movements envisioned a new world supplanting dog-eat-dog capitalism. But over the last half-century that political will and cultural imagination have vanished. Why? THE AGE OF ACQUIESCENCE seeks to solve that mystery. Steve Fraser's account of national transformation brilliantly examines the rise of American capitalism, the visionary attempts to protect the democratic commonwealth, and the great surrender to today's delusional fables of freedom and the politics of fear. Effervescent and razorsharp, THE AGE OF ACQUIESCENCE will be one of the most provocative and talked-about books of the year. "--
"From the American Revolution through the Civil Rights movement, Americans have long mobilized against political, social, and economic privilege. Hierarchies based on inheritance, wealth, and political preferment were treated as obnoxious and a threat to democracy. Mass movements envisioned a new world supplanting dog-eat-dog capitalism. But over the last half-century that political will and cultural imagination have vanished. Why? THE AGE OF ACQUIESCENCE seeks to solve that mystery. Steve Fraser's account of national transformation brilliantly examines the rise of American capitalism, the visionary attempts to protect the democratic commonwealth, and the great surrender to today's delusional fables of freedom and the politics of fear. Effervescent and razorsharp, THE AGE OF ACQUIESCENCE will be one of the most provocative and talked-about books of the year"--
Includes bibliographical references (pages 427-452) and index.
Keywords: BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Corporate Finance; BUSINESS & ECONOMICS / Finance; Social conflict -- United States -- History; Protest movements -- United States -- History; Income distribution -- United States -- History; Elite (Social sciences) -- United States -- History; Power (Social sciences) -- History -- United States; Acquiescence (Psychology) -- History; Social psychology -- History -- United States; United States -- Politics and government -- 1945-